Countering Digital Fitna: An Empirical Study on Hoax-Detection and Islamic Digital Literacy Among Online Muslim Communities - Muhammad Mahfud; Leila Mahdavi; Reza Karimi (Islamic Studies in the World, 2025)
The rapid circulation of misinformation in digital spaces has intensified concerns about “digital fitna,” a term used to describe the spread of deceptive content that distorts religious understanding and destabilizes social cohesion within Muslim online communities. The increasing prevalence of hoaxes, manipulated religious narratives, and misattributed hadith on social media highlights the urgent need for Islamic digital literacy that equips users with both critical thinking skills and authentic religious knowledge. The phenomenon poses serious risks to communal harmony, public trust, and the integrity of Islamic teachings in the digital age. This study aims to examine the effectiveness of hoax-detection skills and the level of Islamic digital literacy among online Muslim communities, with a focus on assessing how users evaluate, verify, and respond to religious misinformation. The research also seeks to identify demographic, cognitive, and behavioral factors that influence susceptibility to digital fitna. A mixed-methods approach was employed, combining quantitative surveys of 312 active Muslim social media users with qualitative interviews involving digital da‘i, Islamic educators, and community moderators. Quantitative data assessed literacy levels and detection accuracy, while qualitative data explored perceptions of misinformation, verification practices, and challenges in navigating religious content online. Findings reveal that while awareness of digital misinformation is relatively high, actual hoax-detection accuracy remains moderate, with only 47% of participants consistently identifying false religious claims. Higher literacy scores are strongly correlated with formal religious education and prior media-literacy training. The study concludes that strengthening Islamic digital literacy requires integrated interventions combining religious authority, technological competence, and community-based verification practices.